Scattering of the Radial Polarized Beams on the Metal Spherical Particle: Plasmonic Nanojet Formation - Plutenko, D. O.; Vasnetsov, M. V. (Frontiers in Physics, 2021)
We report on the effects associated with photonic nanojet (PNJ) formation under illumination of a metallic spherical particle with a focused light beam with polarization singularity. Owing to radial polarization the strongly focused beam generates the on-axis localized structure of intensity in the shadow area of the metal scatterer of different sizes: from Relay particle to microbeads. Significant amplification factor, small transverse size, zero magnetic component on the axis and longitudinal polarization of the electric field are the distinctive features of such structures.